Associations between lifestyle and amyotrophic lateral sclerosis stratified by C9orf72 genotype: a longitudinal, population-based, case-control study. Issue 5 (May 2021) - Westeneng, Henk-Jan; van Veenhuijzen, Kevin; van der Spek, Rick A; Peters, Susan; Visser, Anne E; van Rheenen, Wouter; Veldink, Jan H; van den Berg, Leonard H
Summary: Background: Amyotrophic lateral sclerosis (ALS) is considered to be caused by both genetic and environmental factors. The causal cascade is, however, not known. We aimed to assess lifestyle during the presymptomatic phase of ALS, stratified by C9orf72 mutation, and examine evidence supporting causality of lifestyle factors. Methods: This study was a longitudinal, population-based, case-control study that used data from the Prospective ALS study the Netherlands. We included patients with a C9orf72 mutation (C9+ group), patients without a C9orf72 mutation (C9– group), and controls. Patients fulfilled the revised El Escorial criteria and were recruited through neurologists and rehabilitation physicians in the Netherlands as well as the Dutch Neuromuscular Patient Association and ALS Centrum website. 1322 population-based controls, matched for age and sex, were enrolled via the patients' general practitioners. Blood relatives or spouses of patients were not eligible as controls. We studied the relationship between ALS risk and smoking, alcohol, physical activity, body-mass index (BMI), and energy intake by the use of structured questionnaires. Smoking, physical activity, and BMI were longitudinally assessed up to 50 years before onset (defined as the period before onset of muscle weakness or bulbar symptoms for cases, or age at completing the questionnaire for controls). We calculated posterior probabilities (P(θ|x)) for causal effects of smoking, alcohol, and BMI, using Bayesian instrumental variable analyses. Findings: Between Jan 1, 2006 and Jan 27, 2016, we included 143 patients in the C9+ group, 1322 patients in the C9– group, and 1322 controls. Compared with controls, cigarette pack-years (C9+ group mean difference from control 3·15, 95% CI 0·36 to 5·93, p=0·027; C9– group 3·20, 2·02 to 4·39, p<0·0001) and daily energy intake at symptom onset (C9+ group 712 kJ, 95% CI 212 to 1213, p=0·0053; C9– group 497, 295 to 700, p<0·0001) were higher in the C9+ and C9– groups, whereas current BMI (C9+ group −2·01 kg/m 2, 95% CI −2·73 to −1·29, p<0·0001; C9– group −1·35, −1·64 to −1·06, p<0·0001) and lifetime alcohol consumption (C9+ group −5388 units, 95% CI −9113 to −1663, p=0·0046; C9– group −2185, −3748 to −622, p=0·0062) were lower in the C9+ and C9– groups. Median BMI during the presymptomatic phase for the C9+ group was lower (–0·69 kg/m 2, 95% CI −1·24 to −0·13, p=0·015) and physical activity was similar (–348 metabolic equivalent of task [MET], 95% CI −966 to 270, p=0·27) to controls, whereas both the median BMI during the presymptomatic phase (0·27 kg/m 2, 95% CI 0·04 to 0·50, p=0·022) and physical activity (585 MET, 291 to 878, p=0·0001) were higher in the C9– group than controls. Longitudinal analyses showed more cigarette pack-years in the C9– (starting 47 years pre-onset) and C9+ (starting 24 years pre-onset) groups, and higher physical activity over time in the C9– group (starting >30 years pre-onset). BMI of the C9+ group increased more slowly and was significantly lower (starting at 36 years pre-onset) than in controls, whereas the BMI of the C9– group was higher than controls (23–49 years pre-onset, becoming lower 10 years pre-onset). Instrumental variable analyses supported causal effects of alcohol consumption (P(θ|x)=0·9347) and smoking (P(θ|x)=0·9859) on ALS in the C9– group. We found evidence supporting a causal effect of increased BMI at younger age (mean 33·8 years, SD 11·7) in the C9– group (P[θ|x]=0·9272), but not at older ages. Interpretation: Lifestyle during the presymptomatic phase differs between patients with ALS and controls decades before onset, depends on C9– status, and is probably part of the presymptomatic causal cascade. Identification of modifiable disease-causing lifestyle factors offers opportunities to lower risk of developing neurodegenerative disease. Funding: Netherlands ALS Foundation.